2007
DOI: 10.1080/09602010500505260
|View full text |Cite
|
Sign up to set email alerts
|

Finding out if “The ‘me’ will shut down”: Successful cognitive-behavioural therapy of seizure-related panic symptoms following subarachnoid haemorrhage: A single case report

Abstract: Successful cognitive and behavioural therapies for anxiety disorders in separate cases of acquired brain injury and seizure disorder have been reported although evidence of efficacy is limited. This paper describes the presentation and cognitive-behavioural therapy (CBT) of seizure-related panic symptoms in the context of subarachnoid haemorrhage and cavernoma. Multidisciplinary clinical assessment was conducted and 12 sessions of CBT according to the model of Clark (1986) were delivered. Outcome was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
15
0
3
Order By: Relevance
“…Three studies (54 participants) reported strokes (Lincoln et al 1997;Lincoln and Flannaghan 2003;Gracey et al 2007) and three single-case studies reported encephalitis (McMillan et al 1990;Alderman et al 1995;Dewar and Gracey 2007). In most cases (a total of 744 participants), mixed aetiologies other than TBI or stroke were reported.…”
Section: Primary Diagnosismentioning
confidence: 94%
“…Three studies (54 participants) reported strokes (Lincoln et al 1997;Lincoln and Flannaghan 2003;Gracey et al 2007) and three single-case studies reported encephalitis (McMillan et al 1990;Alderman et al 1995;Dewar and Gracey 2007). In most cases (a total of 744 participants), mixed aetiologies other than TBI or stroke were reported.…”
Section: Primary Diagnosismentioning
confidence: 94%
“…For many people some of the most enduring changes after acquired brain injury relate to the subjective experience of who someone is, or their identity (Cloute, Mitchell, & Yates, 2008;Coetzer, 2008;Gracey, Oldham, & Kritzinger, 2007;Ylvisaker, McPherson, Kayes, & Pellett, 2008), although there is not necessarily a direct link between acquired neurological damage and personhood. Hence "personality change" should probably be conceptualised within a bio-psychosocial framework (Yeates, Gracey, & McGrath, 2008).…”
Section: Emotional Adjustment Grief and Identity Changementioning
confidence: 99%
“…A number of these CBT intervention studies report positive outcomes, improving emotional well-being in distressed (including anxious, traumatised and/or depressed) ABI patient samples. For example, several single case reports have reported beneficial outcomes for traditional CBT-based interventions for the treatment of obsessive-compulsive disorder (OCD) (Williams et al, 2003a), post-traumatic stress disorder (PTSD) (Williams, Evans, & Wilson, 2003b), seizure-related panic attacks (Gracey, Oldham, & Kritzinger, 2007), and depression (Mateer & Sira, 2006), in adults recovering from ABI. There are also a number of group studies reporting positive outcomes.…”
Section: Cbt: Re-examining the Efficacy For Managing Emotional Problementioning
confidence: 99%